Seroepidemiological Survey of Crimean-Congo Hemorrhagic Fever Among Sheep in Mazandaran Province, Northern Iran - Mostafavi, Ehsan (Mary Ann Liebert, Inc., 2012)
Crimean-Congo hemorrhagic fever (CCHF) is a disease prevalent among humans and animals and is endemic in Iran. Although CCHF has been reported in all of its neighboring provinces, in Mazandaran in northern Iran there have been no reports of any cases of human infection. This research has been carried out to clarify the epidemiological aspects of CCHF infection among sheep in various geographical regions of Mazandaran province. In this survey, 270 blood samples were collected from sheep in eastern, central, and western Mazandaran between 2010 and 2011, and the specific ELISA test for CCHF virus was carried out on the blood samples in the National Reference Laboratory in the Pasteur Institute, Tehran, Iran. The CCHF infection rate according to this study was 3.7%. A weak statistical relationship (p=0.063) was seen between the different geographical regions, with a gradual decrease in the infection rate noted, stretching from the eastern to the western portions of the province (eastern 6.8%, central 2.8%, and western 0%). Older sheep were 2.7 times more likely to be infected with the virus (OR 2.70; 95% CI 1.50,4.87; p<0.001). As the infection rate in Mazandaran is low among sheep, and as yet there have been no reports of human infection in this province, CCHF disease is not considered a serious health problem in Mazandaran. It is recommended that further research be carried out on other animals, high-risk human groups, and ticks, in order to more completely reveal the status of the disease in this province.